Analysis of operating systems and procedures in ships and goods services of Inaportsnet-based in the main port of Tanjung Perak Surabaya (Research, Society and Development, 2020)
This research is focused on the main port of Surabaya because the port of Surabaya has a high level of activity in terms of goods loading and unloading services along with the progress of trade. This research was conducted at the Main Port of Tanjung Perak Surabaya. This type of research conducted in this research is to use descriptive research. The results of the study indicate that the Tanjung Perak Main Port of Surabaya has implemented the Inaportnet system to Pelindo III so that since November 2, 2016. The Online-Based System and Procedure of Ship and Goods Services at the Main Port of Tanjung Perak Surabaya is an administrative service procedure for ship and goods service activities since the ship docked at the dock, carrying out loading and unloading operational activities until the ship is designed online so that it can be easily accessed by port service users. The obstacles faced in implementing inaportnet in the main port of Tanjung Perak Surabaya are the inadequate quality of services in the port indicated by the lack of a 24-hour port service system and the lack of loading and unloading facilities. There are still officers directly involved in the service process that do not yet have competence in their fields so that the service process can be constrained if a problem occurs, the network connection system often experiences errors which result in the process of ship and goods service systems not being able to be done online.